HUBUNGAN PENGETAHUAN IBU HAMIL TENTANG TANDA BAHAYA KEHAMILAN DENGAN JUMLAH KUNJUNGAN PEMERIKSAAN ANTENATAL CARE DI WILAYAH KERJA PUSKESMAS PENANAE - Putri Yayu; Jumratun; Nur Islamyati; Jumriani (JKM-Bid: JURNAL KESEHATAN MASYARAKAT KEBIDANAN (The Journal of Public Health Midwifery), 2026)
Background: Antenatal Care (ANC) is the care provided to mothers and fetuses during pregnancy, aimed at improving and maintaining maternal and infant health, preparing for a safe delivery, and reducing maternal mortality and morbidity. Through ANC examinations, pregnant women can more quickly identify danger signs during pregnancy. The recommended standard for ANC visits is at least six visit. during pregnancy. Data from the Bima City Health Office showed that K6 coverage reached 74.30% in 2023, decreased to 71.25% in 2024, and further declined to 38.39% in 2025 (Bima City Health Office, 2025). Meanwhile, K6 coverage at the Penanae Community Health Center in 2025 was 29.91% (Penanae Community Health Center MCH Data, 2025). This study aimed to determine the relationship between pregnant women’s knowledge of pregnancy danger signs and the number of antenatal care visits in the working area of the Penanae Community Health Center, Bima City, in 2025.Methodology: This study employed a quantitative design with a cross-sectional approach. The population consisted of 210 third-trimester pregnant women, with a sample of 42 respondents selected using simple random sampling. Data analysis techniques included univariate and bivariate analyses using the chi-square test. Result: The majority of respondents had poor knowledge, accounting for 17 (40.4%). Most respondents were non-compliant with the recommended ANC visit frequency (≤ 6 visits), totaling 22 (52.4%).